Flower Development: Methods and Protocols - Riechmann, José Luis (Methods in molecular biology, 2014)
Flower Development in Arabidopsis - There is More to it than Learning your ABCs -- Flower Development in the Asterid Lineage -- Grass Flower Development -- Flower Diversity and Angiosperm Diversification -- Flower Development - Open Questions and Future Directions -- Genetic Screens for Floral Mutants in Arabidopsis thaliana: Enhancers and Suppressors -- Genetic and Phenotypic Analysis of Shoot Apical and Floral Meristem Development -- Genetic and Phenotypic Analyses of Petal Development in Arabidopsis -- Cell Biological Analyses of Anther Morphogenesis and Pollen Viability in Arabidopsis and Rice -- Molecular Cell Biology of Male Meiotic Chromosomes and Isolation of Male Meiocytes in Arabidopsis thaliana -- Genetic and Phenotypic Analyses of Carpel Development in Arabidopsis -- Microscopic Analysis of Arabidopsis Ovules -- Scanning Electron Microscopy Analysis of Floral Development -- Detection of mRNA Expression Patterns by Non-radioactive in situ Hybridization on Histological Sections of Floral Tissue -- The GUS Reporter System in Flower Development Studies -- A Floral Induction System for the Study of Early Arabidopsis Flower Development -- Fluorescence Activated Cell Sorting of Shoot Apical Meristem Cell Types -- Translating Ribosome Affinity Purification (TRAP) for Cell-specific Translation Profiling in Developing Flowers -- Laser-assisted Microdissection Applied to Floral Tissues -- Identification of Arabidopsis Knock-out Lines for Genes of Interest -- Gene Expression Analysis by Quantitative Real-time PCR for Floral Tissues -- Misexpression Approaches for the Manipulation of Flower Development -- Next Generation Sequencing Applied to Flower Development: RNA-Seq -- Next-Generation Sequencing Applied to Flower Development: ChIP-Seq -- Live-Imaging of the Arabidopsis Inflorescence Meristem -- Gene Regulatory Network Models for Floral Organ Determination.
Keywords: Blütenbildung